DAMPAK EKONOMI PANDEMI COVID-19 TERHADAP PELAKU USAHA DI INDONESIA - Tri Bayu Sanjaya; Arifin Rosid; Galih Ardin (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2022)
There is a great deal of consensus that in addition to cause adversarial impact on the health sector, Covid-19 pandemic has also caused economic disruption on an unprecendeted scale. However, empirical studies that specifically scrutinise the economic impact of this pandemic in Indonesia are still limited. This study aims to provide a more detailed picture of the economic disruption experienced by Indonesian businesses in the time of the pandemic. Analysing survey data from 12,361 respondents, this paper shows in greater detail the effect of Covid-19 shocks on sales, operating expenses, business capacity, business operational difficulties and status, including marketing and labor-related strategies taken by businesses to maintain their business activities. This study also further analyses the implications of variations in the relationship between business operational difficulties, marketing strategies, and labor-related strategies with the annual turnover and the location of the businesses to show heterogeneity in its impact. Terdapat konsensus bahwa selain berdampak ke sektor kesehatan, pandemi Covid-19 juga memberikan dampak negatif terhadap ekonomi secara luas. Namun, studi empiris yang secara spesifik membahas dampak ekonomi dari pandemi ini di Indonesia masih terbatas. Studi ini bertujuan untuk memberikan gambaran yang lebih detail mengenai dampak ekonomi yang dialami oleh pelaku usaha di Indonesia selama pandemi. Berdasarkan hasil analisis terhadap data dari 12.361 pelaku usaha, studi ini menunjukkan secara detail perubahan penjualan, beban usaha, penggunaan kapasitas usaha, kesulitan operasional usaha yang dihadapi, status operasional usaha, termasuk strategi penjualan dan strategi terkait tenaga kerja yang diambil oleh pelaku usaha untuk mempertahankan aktivitas usaha. Studi ini juga menganalisis lebih jauh implikasi dari variasi hubungan kesulitan operasional usaha, strategi penjualan, dan strategi terkait tenaga kerja dengan omzet dan lokasi dari pelaku usaha untuk melihat dampaknya yang beragam.